Drought sensitivity of three co-occurring conifers within a dry inner Alpine environment - Schuster, Roman (2013)
We applied dendroclimatological techniques to determine long-term stationarity of climate-growth relationships and recent growth trends of three widespread coniferous tree species of the central Austrian Alps, which grow intermixed at dry-mesic sites within a dry inner Alpine environment (750 m asl). Time series of annual increments were developed from > 120 mature trees of Picea abies, Larix decidua and Pinus sylvestris. Calculation of response functions for the period 1911 – 2009 revealed significant differences among species in response to climate variables. While precipitation in May – June favoured radial growth of Picea abies and Larix decidua, Pinus sylvestris growth mainly depended on April – May precipitation. P. abies growth was most sensitive to May – June temperature (inverse relationship). Moving response function coefficients indicated increasing drought sensitivity of all species in recent decades, which is related to a decline in soil moisture availability due to increasing stand density and tree size and higher evapotranspiration rates in a warmer climate. While recent trend in basal area increment (BAI) of L. decidua distinctly declined implying high vulnerability to drought stress, moderately shade-tolerant P. abies showed steadily increasing BAI and quite constant BAI was maintained in drought adapted P. sylvestris, although at lowest level of all species. We conclude that synergistic effects of stand dynamics and climate warming increased drought sensitivity, which changed competitive strength of co-occurring conifers due to differences in inherent adaptive capacity.